Gigahertz-Based Visible Light Detection Enabled via CdS-Coated TiO2 Nanotube Layers - Wiltshire, Benjamin D; Alijani, Mahnaz; Sopha, Hanna Ingrid; Pavlinak, David; Hromádko, Luděk; Zazpe, Raul; Thalluri, Sitaramanjaneya Mouli; Kolibalova, Eva; Macák, Jan; Zarifi, Mohammad H (American Chemical Society, 2023)
Detection of visible light is a key component in material characterization techniques and often a key component of quality or purity control analyses for health and safety applications. Here in this work, to enable visible light detection at gigahertz frequencies, a planar microwave resonator is integrated with high aspect ratio TiO2 nanotube (TNT) layer-sensitized CdS coating using the atomic layer deposition (ALD) technique. This unique method of visible light detection with microwave-based sensing improves integration of the light detection devices with digital technology. The designed planar microwave resonator sensor was implemented and tested with resonant frequency between 8.2 and 8.4 GHz and a resonant amplitude between -15 and -25 dB, depending on the wavelength of the illuminated light illumination on the nanotubes. The ALD CdS coating sensitized the nanotubes in visible light up to similar to 650 nm wavelengths, as characterized by visible spectroscopy. Furthermore, CdS-coated TNT layer integration with the planar resonator sensor allowed for development of a robust microwave sensing platform with improved sensitivity to green and red light (60 and 1300%, respectively) compared to the blank TNT layers. Moreover, the CdS coating of the TNT layer enhanced the sensor's response to light exposure and resulted in shorter recovery times once the light source was removed. Despite having a CdS coating, the sensor was capable of detecting blue and UV light; however, refining the sensitizing layer could potentially enhance its sensitivity to specific wavelengths of light in certain applications.
Detekce viditelného světla na bázi gigahertzů umožněna prostřednictvím nanotrubicovýchvrstev TiO2 potažených vrstvou CdS
Keywords: light detection; visible wavelength range; planar microwave resonator; CdS; atomic layer deposition; resonant structure; TiO2 nanotubes; detekce světla; viditelný rozsah vlnových délek; planární mikrovlnný rezonátor; CdS; depozice atomárních vrstev; rezonanční struktura; TiO2 nanotrubice